Odpowiedzi

2010-01-10T14:41:26+01:00
A)
x=-2y-2
2(-2y-2)-y=1
-4y-4-y=1
-5y=5/:(-5)
y=-1
x=2-2=0

x=0
y=-1

b)
x=-4y-2
3(-4y-2)-8y=10
-12y-6-8y=10
-20y=10+6
-20y=16/:(-20)
y=-0,8
x=3.2-2

x=1.2
y=-0,8
1 5 1
  • Użytkownik Zadane
2010-01-10T15:01:00+01:00
A)x+2y=-2 /-2y
2x-y=1

x=-2y-2
2(-2y-2)-y=1

x=-2y-2
-4y-4-y=1

x=-2y-2
-5y=5

x=-2y-2
y=-1

x=-2*(-1)-2=2-2=0
y=-1

x=0
y=-1

b)x+4y=-2 /-4y
3x-8y=10

x=-4y-2
3(-4y-2)-8y=10

x=-4y-2
-12y-6-8y=10

x=-4y-2
-20y=16

x=-4y-2
y=-4/5

x=-4*(-4/5)-2
y=4/5

x=-3 1/5 -2
y=4/5

x=-5 1/5
y=4/5